2021
DOI: 10.1016/j.bbi.2020.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Association of maternal and infant inflammation with neurodevelopment in HIV-exposed uninfected children in a South African birth cohort

Abstract: Highlights Inflammatory markers were lower in mothers living with HIV. Inflammatory markers were lower in HIV-exposed uninfected infants and children. Early life immune markers predicted impaired motor function at 2 years of age.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 54 publications
2
46
0
Order By: Relevance
“…The kappa was 1.000 and the majority of the included studies were rated as intermediate quality (n = 6), with one [33] rated as high quality. As an inclusion criterion, all study participants had to be treated with ART (or initiate treatment in longitudinal studies).…”
Section: Quality Assessment Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The kappa was 1.000 and the majority of the included studies were rated as intermediate quality (n = 6), with one [33] rated as high quality. As an inclusion criterion, all study participants had to be treated with ART (or initiate treatment in longitudinal studies).…”
Section: Quality Assessment Of the Included Studiesmentioning
confidence: 99%
“…As an inclusion criterion, all study participants had to be treated with ART (or initiate treatment in longitudinal studies). Five studies reported on the duration of therapy (ART exposure) before the respective immune marker assays were conducted [24][25][26]33,34]. In addition, all studies reported the exact ART regimen used (Supplementary Table S1).…”
Section: Quality Assessment Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular importance is the maternal immune activation and inflammation in response to SARS-CoV-2 which has significant potential to cause harm to the developing fetus. Indeed, inflammatory exposures during in the perinatal period have been shown to impair infant growth and development in other disease processes (57) with a particular risk for alterations in brain development and cognitive function later in life (8).…”
Section: Introductionmentioning
confidence: 99%
“…The vulnerability of HEU infants is a likely complex intersection of HIV-exposure immune profile 'remodelling', an 'inflammatory' maternal cytokine milieu 18 , time of antiretroviral therapy (ART) initiation 19 , ART use 20 and prophylactics 21 , increased exposure to maternal viral and bacterial pathogens, and host microbial and environmental factors. Together these result in a more permissive state for the development of infections 1 .…”
Section: Introductionmentioning
confidence: 99%